PERSISTENCE OF TUBERCULOSIS INFECTION IN THE BODY AND LABORATORY DIAGNOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the process of persistence of tuberculosis infection in the body, morphological changes (both specific and nonspecific) are observed in the kidneys. It is known that kidneys take the main load of drug excretion during chemotherapy. In primary tuberculosis, pathologic changes in urine are detected in 28.4% of patients. They are more often observed in children with severe forms of tuberculosis and pronounced intoxication [2, 10, 12]. Leukocyturia and proteinuria are the most frequently detected, while hematuria and cylindruria are less common, which are based on increased vascular permeability of the microcirculatory bed due to immunological mechanisms in response to infection [7,9].